Nutrient Status Of The Soil Layers Of Rice Fields In Taratara Satu District, West Tomohon District Tomohon City - Kamagi, Kamagi; Kumolontang, Wiesje Junnieke Nathsuo; Sinolungan, Meldi Tieneke Magdalena; Rondonuwu, Jenny Jeanette (Sam Ratulangi University, 2024)
Research in the field aims to determine the nutrient status condition in rice fields' soil layers. The things studied are N, P, K, C-organic, soil pH, and soil texture. The research is a survey method with a composite soil sampling technique at 0, 10, and 20 cm depth. Soil samples were taken at six different rice field points in the Taratara area. The nutrient status of N, P, K, and soil pH were analyzed using the Paddy Soil Test Kit (PUTS). C-organic using the Walkley and black method and for soil texture using the pipette method. The data from the analysis is then arranged in table form and explained descriptively. The research results from the six locations studied showed that: 1). N nutrient status is at low status; 2). P nutrient status is low, medium, and high; 3). K nutrient status is at medium and high status; 4). C – Organic nutrient status is at very low and low status and 5). Soil pH is slightly acidic and 6). Soil texture conditions are in the criteria of loam, silty loam, and silty clay loam. Keywords: Nutrient Status, Paddy Soil Layers. Abstrak Penelitian dilakukan di lapangan bertujuan untuk mengetahui kondisi status hara yang ada di lapisan tanah sawah. Hal-hal yang diteliti adalah: N, P, K, C-organik, pH tanah dan tekstur tanah. Metode penelitian adalah metode survei dengan teknik pengambilan sampel tanah perlapisan tanah pada kedalaman 0, 10 dan 20 cm secara komposit. Sampel tanah diambil pada enam titik lahan sawah yang berbeda di wilayah Taratara. Status hara N, P, K dan pH tanah dianalisis menggunakan Perangkat Uji Tanah Sawah (PUTS). C-organik dengan metode Walkley and black dan untuk tekstur tanah dengan metode pipet. Data hasil analisis kemudian disusun dalam bentuk tabel kemudian dijelaskan secara deskriptif. Hasil penelitian dari enam lokasi yang diteliti diperoleh bahwa : 1). Status hara N berada pada status rendah; 2). Status hara P berada pada status rendah, sedang dan tinggi; 3). Status hara K berada pada status sedang dan tinggi; 4). Status hara C – Organik berada pada status sangat rendah dan rendah dan 5). pH tanah berada pada kondisi agak asam serta 6). Kondisi tekstur tanah berada pada kriteria lempung, lempung berdebu dan lempung liat berdebu. Kata kunci : Status Hara, Lapisan Tanah Sawah